Validade fatorial e por critério externo do EPQ-J - Fernanda Maria Franco (2007)
The present dissertation proposes to verify the three-factor structure of personality in children and adolescents and its relation to academic performance. Specifically, it tries to investigate individual differences on the relation among personality development in relation to gender, age and social and anthropometrical variables, not to mention the verification of the relation between self-evaluation of personality and the parentsimpression about their children personality. The sample for this study was composed by 494 students (52,4% male; 47,6% female) aged 8 to 16 years old (X=11,39, SE=1,812) from 3rd to 8th grade of Centro Pedagógico on Universidade Federal de Minas Gerais, participants of the Longitudinal Study for the Evaluation of Psychological Competencies of Schoolchild, accomplished by Laboratório de Avaliação das Diferenças Individuais on the same university. Students with consent signed by parents were subjected to the follow instruments: EPQ-J (collective), TDE (individual) and their anthropometric measures (height and weight) were taken. Besides, Brazils Economical Classification Criterion and Socioeconomic and Adaptive Functioning Questionnaire were fulfilled by parents during the study. Results indicate the presence of the three factors stressed by Eysenck (Psychoticism, Extraversion and Neuroticism), as the presence of the Truth scale. Academic performance was negatively related to Neuroticism and Psychoticism. Age was positively related to Psychoticism and Truth. Parent academic level and Psychoticism presented negative correlation. In terms of parents observation on their children personality, Neuroticism did correlate to fear and dependency, Extraversion to fear, sensation seeking and dependency, Psychoticism with impulsivity, sensation seeking and dependency, Truth did not correlate with any question answered by parents and noise did not correlate to any personality factor. All the exposed correlations, although small, were significant. Mean differences were found to factors in relation to gender, pointing to a higher score of men in Psychoticism and Truth comparing to women. Factors also correlate among themselves. Neuroticism was negatively correlated to Extroversion and positively to Psychoticism and Truth. Extroversion was negatively correlated to Psychoticism, which was positively correlated to Truth. These results support a three-factor model of personality, in children and adolescents, with basis on the factorial and external criterion validation. Data are corroborated by literature, except for the Truth scale, which needs more research for a better comprehension.